Wild ornamental plants of the family Asteraceae from the northeastern part of Azerbaijan (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article deals with wild species of ornamental herbs belonging to the family Asteraceae collected in Quba and Qusar districts of Azerbaijan during 2012–2017. In total, more than 120 specimens were collected and identified based on the main diagnostic morphologic characters. Altogether 49 species belonging to 28 genera and 11 tribes were registered, considering the latest taxonomic and nomenclatural changes. New localities of Cyanus cheiranthifolius and Leontodon danubialis were found in Quba district (the Great Caucasus). The relict species Callicephalus nitens and the Caucasus endemic species Tanacetum leptophyllum were also found in the studied region. The life forms and morphological types, diversity patterns of plants depending on altitude and soil humidity were reflected. Perennial plants, as compared to annuals, are dominant in the districts. Erigeron acris and Lactuca serriola may grow as both annual and/or biennials, while Carduus nutans is mainly biennial. Senecio vernalis may grow as an annual, biennial or perennial plant, depending on its habitats and local conditions. Morphological features, such as root systems, branching patterns, leaf outlines and flowers arrangement, are very variable and depend on the growing environment. Numbers of species occur both in forests and grasslands. Some of them grow along mountain slopes and also occur in meadows. Species variation and a consistent trend along the elevational gradient was observed starting from the low mountain zone. Abundance of species decreased in higher elevations. Results suggest that recent climate warming interacted in changes of habitats of some species. Species distribution patterns along the elevation gradients are affected by mountain range peculiarities, expositions of slopes, soil types, soil sliding processes, and climate warming. Numerous species have been recorded in more than one altitude zone. The number of ornamental wild herbs belonging to Asteraceae growing in these districts can be successfully used in horticulture in parks and gardens.
Keywords: plant diversity, Cyanus cheiranthifolius, Leontodon danubialis, morpholo gy, life forms, growth elevation.